Physical activity and risk of comorbidities in patients with chronic obstructive pulmonary disease: a cohort study - Tsung Yu (Nature Portfolio, 2017)
Chronic lung disease: stay active to avoid depression and anxiety Patients with chronic lung disease who stay physically active could reduce their chances of depression and anxiety. Milo Puhan at the University of Zurich, Switzerland, and co-workers assessed the association between physical activity and the risk of developing various co-existing diseases in 409 patients with chronic obstructive pulmonary disease (COPD). Co-morbidities such as cardiovascular diseases, diabetes and depression are prevalent in patients with COPD, but the reasons why are not clear. Puhan’s team assessed patients’ activity levels using an existing questionnaire, and administered another questionnaire to assess mental health. They followed the cohort for 5 years. Results indicated weak associations between physical activity levels and most physical illnesses, but there were significant links between higher levels of physical activity and a reduced risk of depression and anxiety. The results could inform novel COPD treatment programs.